2013
DOI: 10.1002/jbmr.1936
|View full text |Cite
|
Sign up to set email alerts
|

p130Cas, Crk-Associated Substrate, Plays Important Roles in Osteoclastic Bone Resorption

Abstract: p130Cas, Crk-associated substrate (Cas), is an adaptor/scaffold protein that plays a central role in actin cytoskeletal reorganization. We previously reported that p130Cas is not tyrosine-phosphorylated in osteoclasts derived from Src-deficient mice, which are congenitally osteopetrotic, suggesting that p130Cas serves as a downstream molecule of c-Src and is involved in osteoclastic bone resorption. However, the physiological role of p130Cas in osteoclasts has not yet been confirmed because the p130Cas-deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 52 publications
2
55
0
Order By: Relevance
“…Several studies have shown that Crk and p130Cas play similar roles in regulating actin dynamics (35,37). Furthermore, recent studies have verified that tyrosine phosphorylation of p130Cas is involved in actin organization in osteoclasts (35), and osteoclast-specific p130Cas conditional knockout mice exhibit a high bone mass phenotype caused by a defect in multinucleation and cytoskeleton organization (17). Our present study showed that p130Cas is tyrosine phosphorylated upon stimulation of osteoclastogenic cytokines and subsequently binds CrkII in preosteoclasts (Fig.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Several studies have shown that Crk and p130Cas play similar roles in regulating actin dynamics (35,37). Furthermore, recent studies have verified that tyrosine phosphorylation of p130Cas is involved in actin organization in osteoclasts (35), and osteoclast-specific p130Cas conditional knockout mice exhibit a high bone mass phenotype caused by a defect in multinucleation and cytoskeleton organization (17). Our present study showed that p130Cas is tyrosine phosphorylated upon stimulation of osteoclastogenic cytokines and subsequently binds CrkII in preosteoclasts (Fig.…”
Section: Discussionsupporting
confidence: 68%
“…Recent studies have indicated that p130Cas plays pivotal roles in osteoclasts and engages in complex formation with CrkII in fibroblasts (17,35,36). Therefore, we investigated whether the association between p130Cas and CrkII also regulates osteoclast differentiation.…”
Section: Crkii Enhances Osteoclast Differentiation Through Activationmentioning
confidence: 98%
See 1 more Smart Citation
“…52 Upon binding, various proteins such as c-Src and Pyk2 are recruited with scaffold proteins to transduce a signal required for actin ring formation and bone degradation. 44,45,54,55,56 Interestingly, Rho and Rac activations in response to M-CSF are deficient in αvβ3 integrins knockout osteoclasts. 57 Different approaches have been used to determine the importance of Rho, Cdc42 and Rac in osteoclasts adhesion structures organization but they have often produced contradictory results.…”
Section: Adhesion Structuresmentioning
confidence: 99%
“…We and others showed that Dock5 is part of αvβ3 integrins downstream signaling by forming a Src/Pyk2/p130Cas/ Dock5 complex which ultimately leads to Rac1 activation and localization to the sealing zone. 56,70 On the other hand, Vav3 is activated by M-CSF and adhesion and it is recruited with Rac1 at the plasma membrane of osteoclasts. 71 So Dock5 and Vav3 seem to regulate Rac1 activation at distinct locations in osteoclasts and at different phases of the bone-resorption cycle.…”
Section: Adhesion Structuresmentioning
confidence: 99%